2010
DOI: 10.1111/j.1574-6941.2010.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bacterioplankton assemblages from Karenia brevis bloom and nonbloom water on the west Florida shelf (Gulf of Mexico, USA) using 16S rRNA gene clone libraries

Abstract: The brevetoxin-producing dinoflagellate, Karenia brevis, forms nearly annual blooms off the Florida west coast, severely impacting the region's ecology and economy. Bacteria are often cited as either promoting or interfering with the development of algal blooms, and thus a detailed study of the bacterioplankton assemblages associated with K. brevis was undertaken. We developed sixteen 16S rRNA gene clone libraries from K. brevis bloom and adjacent nonbloom water to determine the bacterial groups present and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 92 publications
1
46
0
Order By: Relevance
“…11B) indicated that Rhodobacterales had statistically positive correlation with the C. polykrikoides populations (p 0.01). Previous reports have indicated that this order was closely correlated with other dinoflagellate blooms formed by Akashiwo sanguinea, Alexandrium spp., Gymnodinium catenatum, Karenia mikimotoi, and Prorocentrum lima (Lafay et al, 1995;Garcé s et al, 2007;Green et al, 2004;Jasti et al, 2005;Jones et al, 2010;Yang et al, 2015). Rhodobacterales is the second most abundant bacterial group in marine environments Rappé et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11B) indicated that Rhodobacterales had statistically positive correlation with the C. polykrikoides populations (p 0.01). Previous reports have indicated that this order was closely correlated with other dinoflagellate blooms formed by Akashiwo sanguinea, Alexandrium spp., Gymnodinium catenatum, Karenia mikimotoi, and Prorocentrum lima (Lafay et al, 1995;Garcé s et al, 2007;Green et al, 2004;Jasti et al, 2005;Jones et al, 2010;Yang et al, 2015). Rhodobacterales is the second most abundant bacterial group in marine environments Rappé et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, large physio-chemical changes may not be essential to initiate blooms of C. polykrikoides as this species has significant ecophysiological tolerance for changes in temperature, salinity, and nutrients (Kudela et al, 2008;Gobler et al, 2012). Recent studies of dinoflagellates have reported that blooms can be closely related to the characteristics of the associated bacteria (Jones et al, 2010 and references therein) with algicidal bacteria perhaps contributing to bloom demise (Mayali and Azam, 2004). The single study to consider bacteria and C. polykrikoides blooms to date reported 10-fold higher bacterial densities associated with C. polykrikoides blooms and used terminal restriction fragment length polymorphisms (T-RFLP) to demonstrate that blooms were associated with a bacterial flora that differed significantly from nearby non-bloom algal populations (Koch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, modern lineages of roseobacters are abundant and consistent components of the phycosphere community of these phytoplankton groups (12,(15)(16)(17)(64)(65)(66)(67). The predicted occurrence of genes involved in motility and chemotaxis in the ancestor of the Roseobacter clade would have potentially allowed cells to sense and swim toward phytoplankton (41), enabled by a cell size of red-plastid-lineage phytoplankton large enough to be detected by chemotaxis (68); earlier-evolving phytoplankton groups dominated by the cyanobacteria and green algal lineages were considerably smaller.…”
Section: Genome Evolutionmentioning
confidence: 99%
“…Roseobacter clade members not only grow on these carbohydrates (e.g., Planktotalea frisia) but also may grow better on exudates produced by certain species (85), raising the possibility of an adaptive association of roseobacters with specific phytoplankton lineages. The organic sulfur compound dimethylsulfoniopropionate (DMSP) is produced in abundance by dinoflagellates and coccolithophorids (12,17,67), two phytoplankton groups often found associated with roseobacters in ocean waters (15,16,(64)(65)(66). DMSP acts as a specific chemical cue that attracts motile and chemotactic bacteria, including roseobacters (86).…”
Section: Roseobacter-phytoplankton Interactionsmentioning
confidence: 99%
“…The UniFrac web interface has been previously utilized to successfully study dynamics of microbial populations in diverse environments such as hot springs, the mammalian intestinal tract and marine phytoplankton blooms (Lozupone et al, 2007;Jones et al, 2010), and we chose this method to differentiate the cyanobacterial populations herein. UniFrac was applied to the ITS sequences from the Maumee River, Maumee Bay, and the western basin of Lake Erie to examine the similarities in the entire cyanobacterial community between the different locations.…”
Section: Unifrac Analysis Of Its Sequencesmentioning
confidence: 99%